The Australian labour market - Ross, Russell (Russell T.); Whitfield, Keith (Sydney : Pearson Education, 2008)
This book examines the key topics in contemporary labour economics It presents the background to current debates and defines the major concepts used by labour economists in an accessible and straighforward manner. The text adopts a pluralistic approach to theory and details government policy.
Machine derived contents note: Chapter 1 Economics of Labour -- 1.1 The Importance of Labour Economics -- 1.2 Economics as an Analytical Discipline 3 -- 1.3 Idiosyncrasies of Labour 5 -- 1.4 Differences of Opinion 8 -- 1.5 M ain Schools of Thought 12 -- 1.6 Methods of Labour Market Research 22 -- 1.7 Conclusions 23 -- Chapter 2 Models of the Labour Market 25 -- 2.1 Labour Market Models 25 -- 2.2 Flexible Wage Models 27 -- 2.3 Rigid Wage Models 33 -- 2.4 Labour Market Models and Public Policy 39 -- 2.5 How the Australian Labour Market Works 42 -- 2.6 Conclusions 46 -- Chapter 3 Use of Quantitative M ethods 49 -- 3.1 Quantitative Methods and Australian Labour Market Research 49 -- 3.2 The Nature of Quantitative Analysis 50 -- 3.3 Types of Data Sets 51 -- 3.4 Types of Variables 53 -- 3.5 Proxies, Noise, and Validity 55 -- 3.6 Statistical Techniques 56 -- 3.7 Statistical Modelling 59 -- 3.8 Functional Form 59 -- 3.9 Beyond Single Studies 62 -- 3.10 Conclusions and Implications 64 -- Appendix 3.1 Introduction to Regression Analysis 65 -- Appendix 3.2 Labour Market Statistics: The Australian Bureau of Statistics and Beyond 67 -- Chapter 4 Employment and ployme71 -- 4.1 Employment and Unemployment in Australia 71 -- 4.2 The Measurement of Employment and Unemployment 73 -- 4.3 Stocks and Flows of Unemployment 82 -- 4.4 H idden U nem ploym ent 86 -- 4.5 A M easure of Labour Underutilisation 91 -- 4.6 Causes of Unemployment 94 -- 4.7 Consequences of Unem ploym ent 96 -- 4.8 C onclusions 97 -- Chapter 5 Patterns of Work 99 -- 5.1 Changing Patterns of Work 99 -- 5.2 Standard and Actual Hours of Work 101 -- 5 .3 P aid L eav e 10 5 -- 5.4 Part-Time Work 108 -- 5.5 How Freely Are Work Hours Chosen? 114 -- 5.6 The Family and Patterns of Work 116 -- 5.7 Income Tax and Patterns of Work 118 -- 5 .8 Conclusion s 120 -- Chapter 6 Disadvantaged Groups in the Workforce 123 -- 6.1 The Nature and Extent of Disadvantage 123 -- 6.2 Theoretical Approaches to Disadvantage 125 -- 6.3 Y oung Persons 130 -- 6.4 O lder Workers 135 -- 6.5 Indigenous Australians 139 -- 6 .6 Migrant Workers 143 -- 6.7 Policies to Address Disadvantage 146 -- 6 .8 Conclusions 14 7 -- Chapter 7 Women in the Workforce 149 -- 7 .1 Introduction 14 9 -- 7.2 Gender Differences in Unemployment and Underutilisation 149 -- 7.3 Occupational and Industrial Segregation 151 -- 7.4 Gender W age Differentials 153 -- 7.5 Equal Pay, Relative Wages and Employment 156 -- 7.6 Policies To Reduce Disadvantage 160 -- 7.7 Conclusions 165 -- Chapter 8 Unions and the Labour Market 167 -- 8.1 The Econom ic Analysis of Unions 167 -- 8.2 Union Membership 17 1 -- 8.3 Unions and the Level of Wages 177 -- 8.4 Unions and Relative Wages 178 -- 8.5 Unions and Industrial Action 184 -- 8. h Closed'i ShopIL 18 -- 8.7: , Unions and 19 -- 8.8 Conclusions I l [ L 19 -- Chapter I 9 Econmic of. Huma Resorce 19 -- 9 . 1 K l Eonoics 19 -- 9.2Peronnl, or Huma Resurc Management? 19 -- 9.31 The 1 Managemen of Huma iR l,l IiiMiesource inl Australia[} 19 -- 9.4 PronlEoo is 19 -- 9 l , , ,5h Personnel...o 19 -- 9,8 Conluions ] 20 -- ChapterI 10 Waes'1I1 ! Polic in", Autr l o 209[ -- 10.2l The [ Australia System of Wag Fiato 210 -- [I10. !he res o Inti on1K } 4 -- 10 .5 D o Central se P o 1I IIIlc 'ies W o k 230 -- 10 .6 Entepris Barga1in1 ing 2 -- 10.7 Conclursions. 4 -- Chapter I In & Labou Market Policy 23 -- 11.1 La ou Make Po lc I 23 -- 11.3 lI Labour Make Po 'licy.- Fin Asrlia 240| -- 11. T raii n in Australia 244 -- 11. Eva ua io of Labou Marke ProgramsIIb L i! 25 -- 11. Conclusions,.
Includes index.
Bibliography: p. [265]-282.
Tertiary students.
Keywords: Labor supply -- Australia; Human capital -- Australia; Unemployment -- Australia; Employment forecasting -- Australia; Industrial relations -- Australia; Collective bargaining -- Australia; Manpower policy -- Australia